2010
DOI: 10.2754/avb201079040587
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity of the Preparation PAX-18 for Juvenile and Embryonic Stages of Zebrafish (Danio rerio)

Abstract: The preparation PAX-18 is a coagulation agent, which is used in water and wastewater treatment facilities and for the treatment of natural waters. The active compound is polyaluminium chloride (9% of Al). The application to the water environment could present a potential risk to different developmental stages of fish. The aim of this study was to assess and compare the toxicity of the preparation PAX-18 for embryonic and juvenile developmental stages of zebrafish (Danio rerio). The acute toxicity tests with ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Cooke et al (2005) and Wauer et al (2004) specified that a safe level should not exceed 0.05 mg Al/L in terms of the dissolved fraction. The experiments of Mácová et al (2010) indicated that the acute toxicity values of PAX-18 (common commercial PAC-type coagulant) found in tests of Danio rerio were 6-13 times higher than the concentration that is usually applied to waters (5-10 mg/ L of Al). Due to the potential long-term effect of coagulant flocs on the aqueous environment, 0.05 mg Al/L seems to be an appropriate reference level for the dissolved form of aluminum.…”
Section: Resultsmentioning
confidence: 99%
“…Cooke et al (2005) and Wauer et al (2004) specified that a safe level should not exceed 0.05 mg Al/L in terms of the dissolved fraction. The experiments of Mácová et al (2010) indicated that the acute toxicity values of PAX-18 (common commercial PAC-type coagulant) found in tests of Danio rerio were 6-13 times higher than the concentration that is usually applied to waters (5-10 mg/ L of Al). Due to the potential long-term effect of coagulant flocs on the aqueous environment, 0.05 mg Al/L seems to be an appropriate reference level for the dissolved form of aluminum.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it can be stated that PAC application at the level used had no or low toxicity effects on the freshwater fauna. Acute toxicity of PAC was studied with juvenile zebrafish (Danio rerio) at approximately 2-3 months of age; the results showed that the mean±standard deviation of the LC50 at 96 hours was 749.7±30.6 mg/l [23]. The actual content of PAC used in the current study was much lower than that of LC50.…”
Section: Water Qualitymentioning
confidence: 70%